The best offer [videorecording (DVD)] - Rush, Geoffrey, 1951-; Sutherland, Donald, 1935-; Sturgess, Jim; Hoeks, Sylvia, 1983- (MPI Media Group, 2014)
When a mysterious heiress asks famed but unscrupulous art appraiser and auctioneer Virgil Oldman to evaluate her late parents' collection yet remains forever unseen behind closed doors, it ignites a spark of curiosity in the normally austere Virgil that soon grows into an all-out obsession. Before long everything in Virgil's carefully constructed life threatens to come apart as he delves ever further into the world of intrigue surrounding his enigmatic employer.